1991
DOI: 10.1016/0303-7207(91)90162-l
|View full text |Cite
|
Sign up to set email alerts
|

In vivo estrogen induction of hepatic estrogen receptor mRNA and correlation with vitellogenin mRNA in rainbow trout

Abstract: SummaryWe have previously described the cloning, sequencing and in vitro expression of a full-length rainbow trout estrogen receptor cDNA (rtER cDNA). This full cDNA randomly labelled was used to study the estrogen induction of hepatic rtER mRNA in correlation with vitellogenin (Vg) mRNA in different physiolo~cal situations.In this paper, we show that in the liver two mRNA species are under hormonal control and their level increases about g-fold after estrogen stimulation.These two mRNAs are expressed and indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
3

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(77 citation statements)
references
References 39 publications
8
65
1
3
Order By: Relevance
“…Interestingly, comparison between immature and mature female rainbow trout showed no increase in the number of grains per PPD or PI cells suggesting that, expression of the ER gene in the pituitary is not strongly regulated by E,. This is clearly different from what has been shown in trout liver by Pakdel et al (1991). Different regulation of rtER mRNA levels according to the cell type in the brain and in the pituitary of rainbow trout has been suggested by Salbert et al (1991).…”
Section: Discussioncontrasting
confidence: 64%
“…Interestingly, comparison between immature and mature female rainbow trout showed no increase in the number of grains per PPD or PI cells suggesting that, expression of the ER gene in the pituitary is not strongly regulated by E,. This is clearly different from what has been shown in trout liver by Pakdel et al (1991). Different regulation of rtER mRNA levels according to the cell type in the brain and in the pituitary of rainbow trout has been suggested by Salbert et al (1991).…”
Section: Discussioncontrasting
confidence: 64%
“…This is further suggested by the fact that the liver esr1 signal overlaps prox1 mRNA (data not shown) an early marker of embryonic liver in zebrafish (Zhao et al, 2007). Expression of esr1 in the liver is likely related to the fact that this organ is an important target tissue for E2 in all oviparous species (Pakdel et al, 1991;Flouriot et al, 1996).…”
Section: Early Estrogen Receptor Expressionmentioning
confidence: 87%
“…1 Collection site of the so-iuy mullet in Liaodong Bay, Bohai Bay, and NanDaiHe in the Bo Sea, and a control site in north China mixed briefly and placed in ice immediately. Syntheses of cDNA were carried out in a 5-μL reaction mixture containing RNase-free water; 1×TaqMan RT buffer; 5.5 mM magnesium chloride; 0.5 mM each of dATP, dGTP, dCTP, and dTTP; 2.5 μM Oligo(dT) 18 ; 0.4 U/μL RNase inhibitor; and 1.25 U/μL of MultiScribe reverse rranscriptase. The RT reaction was carried out for 5 min at 25°C, 5 min at 42°C, and 45 min at 50°C and then inactivated for 15 min at 70°C.…”
Section: Reverse Transcriptionmentioning
confidence: 99%
“…Because the Vtg mRNA expression after E2 injection even at low dose is obvious, however, such variation of β-actin copies can be neglected for the evaluation of Vtg mRNA expression. Published reports [17,18] have suggested that the time course for maximum induction of Vtg mRNA ranges from 16 h to 15 days depending on the species, route of exposure, and doses used. Despite the fact that the optimal time point for mRNA induction may not have been used in the present study, Vtg mRNA expression was induced after single injection for 5 days.…”
Section: A C C T T C T a C A A C G A G C T G A G A G T T G C C C C mentioning
confidence: 99%